Meningkatkan Aktivitas dan Hasil Belajar Menggunakan Model PBL, NHT, Dan TGT Pada Siswa Kelas 4 - Kamsiah; Mahmuddin (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The issue in this study is the low action and learning results. One work to defeat this issue is utilizing the Issue Based Learning, Numbered Head Together, and Groups Games Competition models. The reason for this study was to decide educator action, understudy movement, and understudy learning results. The subjects of this review were fourth grade understudies at SDN Alalak Utara 2 Banjarmasin, adding up to 26 individuals. The exploration technique utilized is a subjective and quantitative methodology with the sort of Homeroom Activity Exploration. Subjective information was gotten through noticing the exercises of instructors and understudies. Information examination in this study utilized enlightening examination procedures and cross-classifications converted into realistic tables and translation utilizing rates. This movement occurred in 4 gatherings, with the consequences of educator action from 25 to 34 with exceptionally dynamic models. Perception of understudy movement traditionally expanded from 42% to 85% with extremely dynamic standards. understudy mental viewpoint gaining results expanded from 31% to 85% (old style). Understudy gaining results from 31% to 85%. In view of this examination, the model is Issue Based Learning, Numbered Head Together, and Groups Games Competition. Can increment educator movement, understudy action and understudy learning results